The history of inclusion in the United States - Osgood, Robert L. (Book collections on Project MUSE., 2005)
"In this comprehensive study, author Robert I. Osgood reveals how the idea of inclusion has evolved into broader realms of thought and practice. In its earliest manifestations, educators dwelled upon the classroom setting itself, wondering whether "disabled" children belonged there; if not, why not; and if so, how could this be accomplished? By the late 1960s, the scope of the discussion had shifted to assess the comprehensive structures of special education and its relationship with general education. The History of Inclusion seamlessly follows this progression into the present decade, in which current educational policy questions the need for any sort of separate "special education" in principle and structure."--Jacket.